2017
DOI: 10.1007/s11482-017-9552-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an adaptation of the Best Possible Self intervention implemented through positive technology: a randomized control trial

Abstract: Context Best possible Self (BPS) is a positive psychological intervention based on positive future thinking. It has been shown to be effective in improving well-being and depressive symptoms over short periods of time. Positive technology is a scientific approach designed to increase well-being through Information and Communication Technologies.Objective To assess the efficacy of the BPS implemented through a positive technology application in improving optimistic thinking, affect and depressive symptoms, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
1
9
1
1
Order By: Relevance
“…Results showed that the BPS exercise produced larger decreases marginally significant in negative expectations after 1-month training compared to the control exercise. These effects are in line with prior results in general population ( Meevissen et al, 2011 ; Enrique et al, 2017a ), indicating that BPS exercise implemented through PT has the ability to decrease negative expectations in patients with ED. This is important given that these patients use to have a pessimistic view about the future ( Malson et al, 2011 ), so that PPIs as the BPS exercise can produce benefits at this level.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Results showed that the BPS exercise produced larger decreases marginally significant in negative expectations after 1-month training compared to the control exercise. These effects are in line with prior results in general population ( Meevissen et al, 2011 ; Enrique et al, 2017a ), indicating that BPS exercise implemented through PT has the ability to decrease negative expectations in patients with ED. This is important given that these patients use to have a pessimistic view about the future ( Malson et al, 2011 ), so that PPIs as the BPS exercise can produce benefits at this level.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the total sample receiving the allocated intervention was composed of 54 participants. During the training, the drop-out rate was 24.1% in the BPS condition and 16% in the control condition and these rates were slightly lower to those obtained in a prior study conducted by our group (26.3% in the BPS condition vs. 20% in the control condition; Enrique et al, 2017a ). A total of seven participants did not respond to the online assessments at the follow-ups.…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations